2016
DOI: 10.1111/jomf.12296
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Gains in Head Start as a Function of Initial Parenting Skill

Abstract: Using data from the Head Start Impact Study (n = 3,696), this article examines whether one year of Head Start differentially benefited parents as a function of their initial parenting behaviors. Four outcomes are examined, namely parents’ rates of engaging in cognitive stimulation, reading to their child, and spanking, as well as their depressive symptoms. In general, most parents demonstrated improvements in their reading practices and cognitive stimulation, regardless of their parenting behaviors at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…These services may help support parents’ skills, capacities, and well-being, such as mental health and education, that are likely to be directly associated with children’s outcomes. Moreover, emerging evidence suggests that direct services for parents can be offered effectively through ECE and lead to both improved parent and child outcomes (Ansari, Purtell, & Gershoff, 2016; Grindal et al, 2016; Harding et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These services may help support parents’ skills, capacities, and well-being, such as mental health and education, that are likely to be directly associated with children’s outcomes. Moreover, emerging evidence suggests that direct services for parents can be offered effectively through ECE and lead to both improved parent and child outcomes (Ansari, Purtell, & Gershoff, 2016; Grindal et al, 2016; Harding et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The ATE for each subgroup was estimated by either restricting the analysis to that subgroup (i.e., subgroup analysis) or including a model parameter which assessed interaction between Head Start and the moderator (i.e., interaction analysis). Alternative methods included estimation of ATE in subgroups defined by post-randomization counterfactual care types in a principal stratification framework ( Feller et al, 2016 ; Zhai et al, 2014 ), and structural equation modeling methods, such as path analysis ( Lipscomb et al, 2013 ), latent class analysis ( Cooper & Lanza, 2014 ), and multiple group analysis ( Ansari et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…For children with parents who were younger ( Lee, 2016 ) or had depressive symptoms ( Miller et al, 2016 ), the effects on cognitive outcomes were not statistically significant. Children with parents who had depressive symptoms at baseline were negatively affected by Head Start on social-emotional outcomes ( Cooper & Lanza, 2014 ) but these parents alleviated their symptoms after one year of Head Start ( Ansari et al, 2016 ). Younger parents were able to advance their education due to their children's Head Start assignment ( Sabol & Chase-Lansdale, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have demonstrated that on average , Head Start has positive but relatively small effects on the frequency with which parents engage in math and literacy activities and on parents’ physical discipline (Ansari et al, 2016; Gelber & Isen, 2013; Puma et al, 2010). Significant average effects do not necessarily signal that treatment effects vary across programs, however, just as null average effects do not mean that there is no variation in impacts.…”
Section: Variation In Head Start Program Effects On Parenting Behaviorsmentioning
confidence: 99%
“…Prior studies examining whether Head Start is effective at enhancing parents’ interactions with their children have found evidence for small to moderate impacts on the frequency with which parents engage in certain reading and math activities with children and their likelihood of spanking children (Ansari et al, 2016; Gelber & Isen, 2013; Puma et al, 2010). Not all Head Start centers are the same, however.…”
mentioning
confidence: 99%